Swimming Australia Annual report 2006-2007 (Annual report Swimming Australia, 2007)
As Swimming Australia moves towards its centenary year (2009), stakeholders and individual members should be buoyed by the continued and sustained achievements of our sport. Swimming in this country is an iconic sport, which provides the public with great performances and a source of national pride. Continued domestic and international success is not guaranteed, and it is the responsibility of all in swimming to ensure such success is achieved. This is a responsibility that Swimming Australia relishes. Our 98th Annual Report details the events, programs and people that make swimming so pre-eminent among Olympic sports. For the fourth year, Swimming Australia reports on its achievements based on its strategic plan - Swimming for Life. The four pillars of the plan are the foundations on which the Swimming Australia Board is building the sport. The achievements and successes of 2006-07 are summarised.